American Head and Neck Society position statement on the use of PD‐1 inhibitors for treatment of advanced cutaneous squamous cell carcinoma. Issue 1 (30th September 2022) - Schmalbach, Cecelia E.; Ow, Thomas J.; Choi, Karen Y.; O'Leary, Miriam; Lin, Alice; Hughley, Brian B.; Emerick, Kevin S.; Moore, Brian; Lee, Nancy Y.; Zandberg, Dan P.; Wang, Steven J.
Abstract: Background: A position statement put forth by the American Head and Neck Society (AHNS) was constructed to provide evidence‐based treatment recommendations for PD‐1 inhibitor use in advanced cutaneous squamous cell carcinoma (cSCC). Secondarily, we sought to identify knowledge gaps warranting further investigation. Methods: A literature search utilizing key terms: cutaneous squamous cell carcinoma, cutaneous cancer, checkpoint inhibitors, systemic therapy, Program Cell Death, PD‐1 (PubMed, Cochrane, and Google Scholar) was carried out to generate evidence‐based statements. The statements were distributed among the AHNS membership. Delphi methodology was applied to identify statements achieving 70% or greater consensus among the leadership team. Results: Twenty‐six position statements achieved consensus. Knowledge gaps for future research included: impact of immunosuppression on cSCC staging and associated treatment; role of PD‐1 inhibitors in immunosuppressed patients. Conclusion: This comprehensive position statement put forth by the AHNS represents majority consensus by practicing head and neck surgeons throughout the country.